Estimate of the incidence of PANDAS and PANS in 3 primary care populations - Wald, Ellen R.; Eickhoff, Jens; Flood, Grace E.; Heinz, Michael V.; Liu, Daniel; Agrawal, Alisha; Morse, Richard P.; Raney, Veronica M.; Veerapandiyan, Aravindhan; Madan, Juliette C. (Frontiers in Pediatrics, 2023)
Abstract Objective Pediatric Autoimmune Neuropsychiatric Disorder Associated with Streptococcal infection (PANDAS) and Pediatric Acute-Onset Neuropsychiatric disorder (PANS) are presumed autoimmune complications of infection or other instigating events. To determine the incidence of these disorders, we performed a retrospective review for the years 2017 – 2019 at three academic medical centers. Methods We identified the population of children receiving well-child care at each institution. Potential cases of PANS and PANDAS were identified by including children age 3-12 years at the time they received one of five new diagnoses: avoidant/restrictive food intake disorder, other specified eating disorder, aversion to food or drink, separation anxiety disorder of childhood, obsessive-compulsive disorder, or other specified disorders involving an immune mechanism, not elsewhere classified. Tic disorders was not used as a diagnostic code to identify cases. Data were abstracted; cases were classified as PANDAS or PANS if standard definitions were met. Results The combined study population consisted of 95,498 individuals. The majority were non-Hispanic Caucasian (85%), 48% were female and the mean age was 7.1 (SD 3.1) years. Of 357 potential cases, there were 13 actual cases (mean age was 6.0 [SD 1.8] years, 46% female and 100% non-Hispanic Caucasian). The estimated annual incidence of PANDAS/PANS was 1/11,765 for children between 3 and 12 years with some variation between different geographic areas. Conclusion Our results indicate that PANDAS/PANS is a rare disorder with substantial heterogeneity across geography and time. A prospective investigation of the same question is warranted.